2022
DOI: 10.2147/ndt.s379985
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Pandemic on Prescribing of Long-Acting Injectable Antipsychotics for Schizophrenia: Results from a United States Prescriber Survey

Abstract: Purpose To describe changes due to the COVID-19 pandemic in the prescribing of long-acting antipsychotics (LAI) for schizophrenia, patient outcomes, and patient and healthcare provider (HCP) attitudes regarding COVID-19 vaccination in the United States (US). Methods An anonymous online survey was administered to US-based LAI prescribers with a psychiatry specialty in May 2021. Information on prescriber and clinical practice characteristics, LAI prescribing, patient outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…However, this result is in line with the recommendations issued by the American Psychiatric Association, which suggested to avoid discontinuation of LAI treatment, particularly in patients in chronic phases of the illness despite the difficulties presented by the pandemic ( Keepers et al., 2020 ), and with the results of other recent studies conducted in the USA ( Gannon et al., 2020 ; Zhdanava et al., 2022 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, this result is in line with the recommendations issued by the American Psychiatric Association, which suggested to avoid discontinuation of LAI treatment, particularly in patients in chronic phases of the illness despite the difficulties presented by the pandemic ( Keepers et al., 2020 ), and with the results of other recent studies conducted in the USA ( Gannon et al., 2020 ; Zhdanava et al., 2022 ).…”
Section: Discussionsupporting
confidence: 88%
“…A recent healthcare provider-based survey reported that the administration and the prescriber-reported adherence to LAI antipsychotics remained substantially stable during the pandemic period in the USA ( Zhdanava et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have suggested that there may be a reduction in LAI initiation. A recent study in Romania found a 48.3% reduction in new LAI prescriptions compared to the pre-pandemic period [ 57 ], whereas in the US, LAI prescribing remained unchanged in 64.6% of cases, according to a survey among 401 LAI prescribers [ 58 ]. However, other research yielded different results.…”
Section: Discussionmentioning
confidence: 99%
“…I read with interest Zhdanava et al’s article titled: “Impact of COVID-19 pandemic on prescribing of long-acting injectable antipsychotics for schizophrenia: Results from a United States prescriber survey”, 1 in which the authors stated that, of 401 long-acting injectable (LAI) prescribers in their study, 64.6% reported no change to their LAI prescriptions during the COVID-19 pandemic. Moreover, 50% of LAI prescribers reported no change in adherence rates to oral antipsychotic medications.…”
Section: Dear Editormentioning
confidence: 99%
“… 3 The present study and that of Ifteni et al also raised concerns regarding online medical care. 1 , 4 In terms of LAI treatment, Ifteni et al showed that extending the frequency of administration as much as possible during the COVID-19 pandemic was desirable. 4 Our study also showed higher expectations for longer formulation of atypical antipsychotics.…”
Section: Dear Editormentioning
confidence: 99%